Decreased Estimated Glomerular Filtration Rate and Proteinuria and Long-Term Outcomes After Ischemic Stroke: A Longitudinal Observational Cohort Study. Issue 5 (6th April 2023) - Ueki, Kana; Matsuo, Ryu; Kuwashiro, Takahiro; Irie, Fumi; Wakisaka, Yoshinobu; Ago, Tetsuro; Kamouchi, Masahiro; Kitazono, Takanari; ,
Abstract : Background: It remains unclear how chronic kidney disease and its underlying pathological conditions, kidney dysfunction, and kidney damage, are associated with cardiovascular outcomes. This study aimed to determine whether kidney dysfunction (ie, decreased estimated glomerular filtration rate), kidney damage (ie, proteinuria), or both are associated with the long-term outcomes after ischemic stroke. Methods: A total of 12 576 patients (mean age, 73.0±12.6 years; 41.3% women) with ischemic stroke who were registered in a hospital-based multicenter registry, Fukuoka Stroke Registry, between June 2007 and September 2019, were prospectively followed up after stroke onset. Kidney function was assessed by estimated glomerular filtration rate and categorized into G1: ≥60 mL/(min·1.73 m 2 ), G2: 45–59 mL/(min·1.73 m 2 ), and G3: <45 mL/(min·1.73 m 2 ). Kidney damage was evaluated by proteinuria using a urine dipstick test and classified into P1: −, P2: ±/1+, and P3: ≥2+. Hazard ratios and 95% CI for events of interest were estimated by a Cox proportional hazards model. Long-term outcomes included recurrence of stroke and all-cause death. Results: During the median follow-up of 4.3 years (interquartile range, 2.1–7.3 years), 2481 patients had recurrent stroke (48.0/1000 patient-years) and 4032 patients died (67.3/1000 patient-years). Chronic kidney disease was independently associated with increased risks of stroke recurrence and all-cause death even after adjustment for multiple confounding factors, including traditional cardiovascular risk factors. Both estimated glomerular filtration rate and proteinuria were independently associated with increased risks of stroke recurrence (multivariable-adjusted hazard ratio [95% CI], G3: 1.22 [1.09–1.37] versus G1, P3: 1.25 [1.07–1.46] versus P1) and death (G3: 1.45 [1.33–1.57] versus G1, P3: 1.62 [1.45–1.81] versus P1). In subgroup analyses, effect modifications were found in the association of proteinuria with death by age and stroke subtype. Conclusions: Kidney dysfunction and kidney damage were independently, but differently, associated with increased risks of recurrent stroke and all-cause death.